Psychological, interpersonal, and clinical factors predicting time spent on physical activity among Mexican patients with hypertension - Ybarra Sagarduy, José Luis; Camacho Mata, Dacia Yurima; Moral de la Rubia, José; Piña López, Julio Alfonso; Yunes Zárraga, José Luis Masud (Dove Medical Press, 2018)
Background: It is widely known that physical activity is the key to the optimal management and clinical control of hypertension. Purpose: This research was conducted to identify factors that can predict the time spent on physical activity among Mexican adults with hypertension. Methods: This cross-sectional study was conducted among 182 Mexican patients with hypertension, who completed a set of self-administered questionnaires related to personality, social support, and medical adherence and health care behaviors, body mass index, and time since the disease diagnosis. Several path analyses were performed in order to test the predictors of the study behavior. Results: Lower tolerance to frustration, more tolerance to ambiguity, more effective social support, and less time since the disease diagnosis predicted more time spent on physical activity, accounting for 13.3% of the total variance. The final model shows a good fit to the sample data (pBS =0.235, χ2/gl =1.519, Jöreskog and Sörbom’s Goodness of Fit Index =0.987, adjusted modality =0.962, Bollen’s Incremental Fit Index =0.981, Bentler-Bonett Normed Fit Index =0.946, standardized root mean square residual =0.053). Conclusion: The performance of physical activity in patients with hypertension depends on a complex set of interactions between personal, interpersonal, and clinical variables. Understanding how these factors interact might enhance the design of interdisciplinary intervention programs so that quality of life of patients with hypertension improves and they might be able to manage and control their disease well. Keywords: physical activity, hypertension, personality, social support, time since diagnosis, intervention programs